Entrepreneurial Potential and Gender Effects: The Role of Personality Traits in University Students’ Entrepreneurial Intentions - Ward, Alexander; Hernández-Sánchez, Brizeida R.; Sánchez-García, Jose C. (Frontiers in Psychology, 2019)
The percentage of female entrepreneurs is far below the level of males, although it has increased over the past several years. Based on the theory of planned behavior, the purpose of this article is to specify a model in which the relationship among entrepreneurial potential, gender and entrepreneurial intention are explored, by analyzing how perceived behavioral control and perceived entrepreneurial skills, as exogenous variables, affect expression of intention for business, and how these are mediated by their entrepreneurial motivations and risk taking propensity. Control variables where also included in this model, such as necessity-driven motives for business, in order to observe whether these are an influential factor. An implementation of Structural Equation Modeling was used to analyze data collected from 677 students. Variables within the model were compared by gender using t-Test, and all multivariate analysis were done by each one separately as well, in order to better gauge their perceptions. Results showed that mean differences between males and females are not abundant, and come only from intentions, perceived behavioral control and subjective norm, which are higher in males; and motives for business higher in females. Multivariate analysis shows gender differences at the mediation level and that necessity-driven motives are an influencing factor, more so in males, and it hampers the significance of subjective norm. Finally, the theoretical and practical implications of the results within the framework of entrepreneurship in Spain and future alternatives to improve the entrepreneurial potential are discussed.